2020
DOI: 10.1016/j.jaac.2019.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Personalized Risk of Mood Recurrences in Youths and Young Adults With Bipolar Spectrum Disorder

Abstract: Objective: With each recurrence the prognosis of bipolar disorder (BD) worsens, indicating the need to identify the factors associated with increased recurrence risk. The course of BD is heterogenous and although risk factors for recurrence for the group as a whole have been reported in the literature, identification of risk factors for a specific individual are crucial for developing personalized treatments.Method: 363 recovered BD youths/young adults from the Course and Outcome of Bipolar Youth (COBY) study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…The RC was trained via boosted multinomial classification trees, 29 a useful model for these data because it implicitly incorporates interactions between predictors and has been shown to effectively predict mood episodes in COBY and elsewhere 17,30 . Predictions were then calibrated via Platt scaling 31 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RC was trained via boosted multinomial classification trees, 29 a useful model for these data because it implicitly incorporates interactions between predictors and has been shown to effectively predict mood episodes in COBY and elsewhere 17,30 . Predictions were then calibrated via Platt scaling 31 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, RCs have been developed to predict course and treatment response in psychiatric disorders including psychosis 11 and depression 14 . Our group developed RCs to predict 5‐year bipolar disorder onset among offspring of parents with bipolar disorder, 15 risk for progression from bipolar, not otherwise specified (NOS), to bipolar‐I/‐II among youth, 16 and risk for mood recurrence among young adults with bipolar disorder 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the course BD is heterogeneous, in a substantial group of patients, the risk of recurrence increases with the number of previous episodes. 53 , 143 Overall, the model of staging has helped clinicians to appreciate the importance of early identification and treatment in BD. 144 Models of staging do not imply a uniform or inevitable progression from less severe to more complicated presentations.…”
Section: Proposed Terminologymentioning
confidence: 99%
“…Previous COBY analyses assessed differences between youth with child‐ and adolescent‐onset BD at intake and found that youth with child‐onset (vs. adolescent‐onset) BD had higher levels of mood liability during manic/hypomanic episodes, higher rates of attention deficit hyperactivity disorder (ADHD) and lower rates of substance use disorder (SUD), and higher rates of family history of both mood and non‐mood psychopathology 15,16 . While analyses from the COBY study indicate that mood symptoms in general persist into young adulthood for these youth, 17,18 the presence versus absence of mania/hypomania in young adulthood, and how this may differ for youth with child‐ versus adolescent‐onset mania/hypomania, have not been directly assessed. In fact, to our knowledge, there have not been any clinical studies to prospectively assess the continuity of mania/hypomania across childhood, adolescence, and young adulthood.…”
Section: Introductionmentioning
confidence: 99%